Attitudes of the 3rd Grade Students at Intermediate Schools towards Using Virtual Museum in Arabic Language Course (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to investigate the attitudes of the 3rd grade students at intermediate school towards the virtual museum in the Arabic language course in Jeddah. To achieve this objective, a virtual museum and an attitude scale were designed by the researchers. The descriptive approach was used to suit the nature of the study. The sample was consisted of a simple random sample of (35) students. They were taught by using the virtual museum and then the attitude scale was applied to them. The data were statistically analyzed by using the (Kruskal-Wallis) test to check the existence of differences among the four attitudes. It was concluded that there were no statistically significant differences at the significance level of 0.05 among the students. In light of this result, a set of recommendations were given, including: providing training programs and intensive workshops for teachers to help them to deal with virtual museums to improve teaching Arabic language courses. In addition, it is necessary to integrate virtual museum into Arabic and other fields.
Keywords: Virtual Museums; Attitudes; Intermediate Schools; Arabic Language Course